Influence of meteorological conditions and crown defoliation on tree phenology in intensive forest monitoring plots in Slovenia - Vilhar, Urša (Acta silvae et ligni, 2014)
Data from the forest monitoring programme in Slovenia were used to assess the relationship between tree phenology, crown defoliation and meteorological conditions in Fagus sylvatica, Quercus robur and Picea abies forests in the 2004-2013 period. We hypothesized a species-specific response of first leaf unfolding, general leaf colouring, the length of the growing season to crown defoliation, air temperature, precipitation and soil water. In accordance with the hypothesis, we found a high sensitivity of first leaf unfolding to air temperature and precipitation for all species, exhibiting contrasting responses. We observed strong sensitivity of beech defoliation to precipitation and soil water conditions. Oak crown defoliation and next-year phenology were correlated, with higher crown defoliation contributing to earlier leaf unfolding, later autumn leaf colouring and longer growing season of oak in next year. Correlation between crown defoliation and phenology was found neither for beech nor spruce.
Keywords: gozni ekosistemi; fenologija dreves; osutost krošenj; temperatura zraka; padavine; tla; vsebnov vode v tleh; Slovenia; Slovenija